Maternal Complications in Obese Women During Pregnancy - Nazir, Anita; Mushtaq, Rubina (Indus Journal of Bioscience Research, 2025)
Background: Obesity during pregnancy has emerged as a major public health issue, contributing to multiple maternal complications that jeopardize both maternal and neonatal outcomes. Metabolic, hypertensive, and infectious disorders occur more frequently in obese expectant women, yet their burden in Pakistan remains underexplored. Objective: To determine the frequency of maternal complications in obese women during pregnancy. Study Design: Descriptive study. Duration and Place of Study: The study was carried out from February 2025 to May 2025 at the Department of Obstetrics and Gynaecology, Rawal Institute of Health Sciences, Islamabad. Methodology: A total of 369 obese pregnant women, aged 18–40 years with singleton pregnancies beyond 12 weeks of gestation, were included through non-probability consecutive sampling. Women with pre-existing diabetes, thyroid disorders, or congenital fetal anomalies were excluded. Obesity was defined as body mass index >30 kg/m². Standard diagnostic criteria were used to identify maternal complications. Results: The mean age of participants was 29.75 ± 4.76 years, mean BMI 34.34 ± 2.40 kg/m², and mean gestational age 27.37 ± 5.37 weeks. Impaired glucose tolerance was observed in 15.2%, gestational diabetes in 19.8%, pregnancy-induced hypertension in 20.1%, urinary tract infection in 17.6%, and vaginal candidiasis in 24.9% of women. Stratified analysis revealed significant associations of urinary tract infection with higher parity (p